2007
DOI: 10.1534/genetics.106.064576
|View full text |Cite
|
Sign up to set email alerts
|

Translation Initiation inSaccharomyces cerevisiaeMitochondria: Functional Interactions Among Mitochondrial Ribosomal Protein Rsm28p, Initiation Factor 2, Methionyl-tRNA-Formyltransferase and Novel Protein Rmd9p

Abstract: Rsm28p is a dispensable component of the mitochondrial ribosomal small subunit in Saccharomyces cerevisiae that is not related to known proteins found in bacteria. It was identified as a dominant suppressor of certain mitochondrial mutations that reduced translation of the COX2 mRNA. To explore further the function of Rsm28p, we isolated mutations in other genes that caused a synthetic respiratory defective phenotype together with rsm28D. These mutations identified three nuclear genes: IFM1, which encodes the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 66 publications
5
43
0
Order By: Relevance
“…Thus, the absence of Rmd9p leads to some mtDNA instability on glucose-rich medium. However, the absence of Rmd9p leads to the rapid loss of mtDNA in the strains whose mtDNA contains introns (Williams et al 2007, this issue; data not shown).…”
Section: Resultsmentioning
confidence: 91%
“…Thus, the absence of Rmd9p leads to some mtDNA instability on glucose-rich medium. However, the absence of Rmd9p leads to the rapid loss of mtDNA in the strains whose mtDNA contains introns (Williams et al 2007, this issue; data not shown).…”
Section: Resultsmentioning
confidence: 91%
“…The function(s) of the PPR motifs shared by these four proteins are not known in any detail, but PPR motifs have been implicated in RNA binding and post-transcriptional gene regulation in organelles, including transcript processing and stabilization, tRNA binding, and translation (42,60,61). The discovery that Aep3p (this work) and Rmd9p (49) are also functionally linked to mitochondrial translation initiation factors suggests that the coupling between mRNA stability and translation may be a general phenomenon mediated by RNA-binding proteins and occurs mechanistically at the initiation stage.…”
Section: Discussionmentioning
confidence: 89%
“…Genetic interaction with the genes encoding methionyl-tRNA formyltransferase and ymIF2 provides strong evidence that Rsm28p has a role in translation initiation. Williams et al (49) speculate that the small subunit protein Rsm28p might provide IF1 and/or IF3-like functions in yeast mitochondrial translation initiation.…”
Section: Discussionmentioning
confidence: 99%
“…In S. cerevisiae, Rmd9 encodes a PPR protein and the gene was isolated in two independent screens: as a multi-copy suppressor of point mutations in Oxa1, which encodes an inner membrane insertase for newly translated mitochondrial proteins ( Table 2), and as a synthetic respiratory defective mutant of the deletion of a small ribosomal subunit gene, Rsm28 (Δrsm28 alone only leads to a partial respiratory deficiency) ( Table 2). 19,30 It was also shown that a small fraction of Rmd9 co-sediments with the small subunit of the mitochondrial ribosome in sucrose gradients. Thus, Rmd9 interacts with the ribosome but is not a ribosomal subunit per se.…”
Section: Principal Steps Of Mitochondrial Gene Expression Affected Bymentioning
confidence: 99%